Protective role of taurine in developing offspring affected by maternal alcohol consumption - Pilant Ananchaipatana-Auitragoon (2018)
© 2015, Leibniz Research Centre for Working Environment and Human Factors. All rights reserved. Maternal alcohol consumption is known to affect offspring growth and development, including growth deficits, physical anomalies, impaired brain functions and behavioral disturbances. Taurine, a sulfur-containing amino acid, is essential during development, and continually found to be protective against neurotoxicity and various tissue damages including those from alcohol exposure. However, it is still unknown whether taurine can exert its protection during development of central nervous system and whether it can reverse alcohol damages on developed brain later in life. This study aims to investigate protective roles of taurine against maternal alcohol consumption on growth and development of offspring. The experimental protocol was conducted using ICR-outbred pregnant mice given 10% alcohol, with or without maternal taurine supplementation during gestation and lactation. Pregnancy outcomes, offspring mortality and successive bodyweight until adult were monitored. Adult offspring is supplemented taurine to verify its ability to reverse damages on learning and memory through a water maze task performance. Our results demonstrate that offspring of maternal alcohol exposure, together with maternal taurine supplementation show conserved learning and memory, while that of offspring treated taurine later in life are disturbed. Taurine provides neuroprotective effects and preserves learning and memory processes when given together with maternal alcohol consumption, but not shown such effects when given exclusively in offspring.